Returning to Campus After Study Abroad : Differences in Intercultural Competency and Adaptability Based on Structure of Study Abroad Program - Fay, Martha J.; Wallace, Danielle; Rowe, Graham; Forsha, Katie; Hayden, Brett; Cornett, Cora (My University, 2018)
Institutions of higher education face mounting pressures to stay on the cutting edge of opportunity availability as incoming students realize the demands of the increasingly globalized workforce of which they plan to enter. The availability and quality of a university's study abroad/international immersion programs is at the forefront of many students' minds when choosing an institution of higher education. This study examines the potential associations between the structure of a study abroad/international immersion program and the sojourner outcomes of intercultural competency and adaptability as previous research suggests that the length of program alone does not correlate with these outcomes.
Color poster with text, tables, and images.
Keywords: Posters; Study abroad; International students--Wisconsin--Eau Claire; International students